التضامن الجزائري مع انتفاضة الشعب المغربي هجومات 02 أوت 1955 - ومان, حورية; تلمساني, بن يوسف (Sciences de l'Homme et de la Société, 2017)
الملخص: مع تطور النشاط الثوري في المنطقة ورفض بعض عناصر المقاومة التونسية والمغربية لوضع سلاحهم واقتناعهم بوحدة كفاح المغاربي المسلح إلى جانب الثورة التحريرية الجزائرية. ساهمت هذه الأخيرة في دعم هاتين المقاومتين لاستمرار نشاطهم الثوري. ومن مظاهر هذه المساهمة دعمها للشعب المغربي الشقيق في انتفاضته يوم 02 أوت 1955 بمناسبة الذكرى الثانية لنفي ملك المغرب محمد الخامس. والتي تزامنت مع هجومات 02 أوت 1955في الشمال القسنطيني بقيادة زيغود يوسف. Abstract: With the development of the revolutionary armed activities in the region,som from the Tunisian and Moroccan resistance rejected to put down their arms and get convinced to unify with the armed struggle of the Maghreb with that of the Algerian revolution.The latter contributed to support these two resistances for the continuation of their revolutionary activities. This contribution could be seen in its support of the brotherly Moroccan people in their uprising on 20 August 1955 on the occasion of the second anniversary of the exiled King Mohmmed V of Morocco,W hich coincided With the attacks of 20August 1955 in the North ; led by youcef Zighoud from Constanine.